RDC review Jan 2004: Bulletin for Research and Development UiTM - UiTM, Institute of Research, Development and Commercialization (Institute of Research, Development and Commercialization, 2004)
IRDC Review takes a short walk down memory lane to recap on some of the significant issues and events that impacted the Institute in the past year. Indeed it has been a year of achievements at the Institute of Research, Development and Commercialisation (IRDC) and much progress has been recorded in the year 2003. A testimony of this is the certification award of the MS ISO 9001:2000 Quality Management Systems Certification to IRDC in April 2003 for its management of research and consultancy activities.